DESIGN OF AN ERGONOMIC TROLLEY FOR PELVIC WORKERS BASED ON ANTHROPOMETRIC ANALYSIS: PERANCANGAN TROLI BARANG ERGONOMIS UNTUK KULI ANGKUT BERDASARKAN ANALISIS ANTROPOMETR - Daniel Marcello; Seli; Petra Putri Ardika; Calvin Cornelius Simanjuntak; Heri Setiawan (PROGRAM STUDI TEKNIK INDUSTRI UNIVERSITAS TRIDINANTI, 2024)
The job of a porter is often synonymous with unergonomic working conditions and high risks to health. This is caused by a mismatch in the working posture of porters. Therefore, this research aims to design an ergonomic goods trolley for porters based on anthropometric analysis. This research uses a participatorydesign method that involves porters in the design process. The porters' anthropometric data is measured and analyzed to determine optimal trolley dimensions. Based on the data that has been taken, the researchresults show that the ergonomically designed goods trolley has dimensions that suit the dimensions and body posture of porters. So it can reduce the workload and increase the comfort of porters, such as wheels that rotate easily and sufficient storage space. In conclusion, designing ergonomic goods trolleys for porters can improve the health and safety of porters. This trolley can be a solution to overcome the health problems that porters often experience due to work.